Mucosal Heterologous Prime/Boost Vaccination Induces Polyfunctional Systemic Immunity, Improving Protection Against Trypanosoma cruzi - Sanchez Alberti, Andrés; Bivona, Augusto E.; Matos, Marina N.; Cerny, Natacha; Schulze, Kai; Weißmann, Sebastian; Ebensen, Thomas; González, Germán; Morales, Celina; Cardoso, Alejandro C.; Cazorla, Silvia I.; Guzmán, Carlos A.; et al. (Frontiers in Immunology, 2020)
There are several unmet needs in modern immunology. Among them, vaccines against parasitic diseases and chronic infections are leading. Trypanosoma cruzi, the causative agent of Chagas disease is an excellent example of this issue producing a silent parasitic invasion but still affecting millions of people worldwide due to progression into the symptomatic chronic phase of infection. In search for novel vaccines candidates, we have previously introduced Traspain, an engineered trivalent immunogen that was designed to address some of the known mechanism of T. cruzi immune evasion. Here, we analyzed its performance in different DNA prime/protein boost protocols and characterized the systemic immune response associated with diverse levels of protection. Formulations that include a STING agonist like c-di-AMP in the boost doses, were able to prime a Th1/Th17 immune response. Moreover, comparison between them showed that vaccines that were able to prime polyfunctional cell-mediated immunity at the CD4 and CD8 compartment enhanced protection levels in the murine model. These findings contribute to a better knowledge of the desired vaccine-elicited immunity against T. cruzi and promote the definition of a vaccine correlate of protection against the infection.